How to measure the status quo bias? A review of current literature - Marie-E. Godefroid; Ralf Plattfaut; Björn Niehaves (Management Review Quarterly, 2022)
The Status Quo Bias (SQB) describes an individual's preference to avoid changes and maintain the current situation. In today's world, technological advances require nearly constant change within organizations. Thus, SQB can become an issue when it hinders progress. Therefore, it is crucial to understand how this effect can be reliably measured and, even more importantly, what countermeasures to employ. Prior research has focused more on individual measuring approaches and less on countermeasures. As researchers across different research fields have studied this bias, we conduct a literature review spanning different scholarly fields. This broader research focus allows us to identify four measurement approaches and 13 countermeasures along the three aspects of cognitive misperception, rational decision making, and psychological commitment of SQB. Our overview consolidates existing knowledge and will hopefully be the starting point for researchers to start combating this bias where needed. Successful and proven countermeasures can, for example, increase the acceptance and adoption of digital innovations and technology in general and thereby allow organizations to capitalize on their investments.
Keywords: D91; 650; Status quo bias; Literature review; Cognitive bias; Bias measurement; Countermeasures